BUNYI-BUNYIAN PANCAGITA DALAM UPACARA ODALAN DI KABUPATEN KARANGASEM BALI - , I WAYAN SENEN; , Prof. Dr. R. M. Soedarsono ([Yogyakarta] : Universitas Gadjah Mada, 2013)
It is a very interesting thing to research on a religious ritual of Hindu Karangasem Regency that there is vagueness regarding the supporting factors in the lively and merry atmosphere, the characteristics of use and meaning of the sounds of pancagita in odalan ceremony which until the present time have not been profoundly studied by previous researchers although such aspects are very important to be formulated and informed. This qualitative study employed a field research involving selection of location, selection of resource persons, determination of research instrument, data collection, data analysis and data presentation. In regard to its uniqueness, Karangasem Regency was selected as the research location. The resource persons were selected based on the relevance of the competence to the research. The research instrument was determined based on the need of the research process. Data were collected through observation, library research, interview and documentation. Data were analyzed by using the concepts and theories of text, ritual, religion, aesthetics and semiotics. Meanwhile, the data were presented qualitativedescriptively. The research result indicates that the emergence of the lively and merry atmosphere on the sounds of pancagita is supported by the teaching of siwa sidhanta, concept of freedom, concept of karma, aesthetic concept and pancadewata concept. The characteristics of use of sounds in odalan ceremony are that it is presented in a series of odalan ceremony, conditioned through spiritually sacred process and presented in a sacred space, time and condition. It is revealed that there are three meanings of the sounds of pancagita, namely iconic meaning, indexical meaning and symbolic meaning. Therefore, it can be inferred that 1) the lively method to reach God is still relevant to the soul of modern society. 2) All kinds of sounds may be used as the sounds of odalan ritual subject to certain conditions. 3) The pancagita sounds are an actualization of sense of respect of the devotee to the devoted, sense of unity between fellow human beings and sense of beauty of the ceremony participants and audience.